Long-term results of coronary artery bypass grafting in women under 45 years of age - Zwoliński, Radosław; Ostrowski, Stanisław; Walczak, Andrzej; Banyś, Andrzej; Dziuba, Michał; Marcinkiewicz, Anna; Jaszewski, Ryszard (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Objectives: The occurrence of myocardial infarction and advanced atheromatosis of coronary arteries in premenopausal women is unusual. Aim of the study: The aim of the study was to assess the clinical outcome of coronary artery bypass grafting in a population of women under 45 years of age. Material and methods : From 1990 to 1999, 58 women aged 27 to 45 (mean 41.5) years were discharged from hospital after coronary artery bypass grafting (CABG). The mean rate of grafts was 2.6 ±1.1 and revascularization completeness was 91.4%. The left internal mammary artery was used in 96.5% of cases. Results : The mean follow-up period was 17.5 years. The 5, 10 and 15 year overall survival rates for patients discharged from the hospital were 88%, 81.5%, 66% respectively. Angina free and coronary events free survival 5, 10 and 15 years post surgery was 66%, 57%, 36.5% respectively. The mean CCS class was 3.24, 5 years after CABG 1.48, 10 years after 1.7. Mean NYHA class 2.51, 1.78, 1.65 respectively. In 9 of 12 patients who underwent re-coronarography, percutaneous coronary angioplasty (PCI) was carried out, mainly in smokers. Conclusion : The long-term results of CABG in young women are good, especially regarding the quality of life. Postoperatively observed decrease of patients’ professional activity was due to a subjective feeling of disease as well as reasons other than medical. Continuing cigarette smoking is the main cause of unsatisfactory clinical outcome after CABG. The study population was markedly exposed to the occurrence of menopause before age of 45 years.